Noninvasive Prenatal Testing as Compared to Chorionic Villus Sampling Is More Sensitive for the Detection of Confined Placental Mosaicism Involving the Cytotrophoblast. Issue 2 (February 2021) - Van Opstal, Diane; Eggenhuizen, Geerke M.; Joosten, Marieke; Diderich, Karin; Govaerts, Lutgarde; Galjaard, Robert-Jan; Go, Attie; Knapen, Maarten; Boter, Marjan; Cheung, Wai Y.; van Koetsveld, Nicole; van Veen, Stefanie; et al.
Abstract : (Abstracted from Prenat Diagn 2020;40:1338–1342) Confined placental mosaicism (CPM) describes a chromosomally abnormal placenta with a chromosomally normal fetus. Confined prenatal mosaicism may be detected prenatally by either chorionic villus sampling (CVS) or noninvasive prenatal testing (NIPT) using cell-free DNA (cfDNA), which evaluates the DNA released from cytotrophoblast (CTB) into maternal blood.